The Responsibility of Canadian Counselling Psychology to Reach Systems, Organizations, and Policy-Makers - Evans, Hilary; Russell-Mayhew, Shelly (Canadian Journal of Counselling and Psychotherapy, 2020)
Social justice is becoming an increasingly important aspect of counselling psychology in Canada, and more research is needed to understand how to make a difference outside of one-on-one counselling sessions. Twelve individuals (including students, researchers, clinicians, and professors) comprised a working group entitled “The Responsibility of Canadian Counselling Psychology to Reach Systems, Organizations, and Policy-Makers” and discussed the role of counselling psychology in reaching beyond individual change. Discussion generated three main themes: identifying needs, using our unique training, and infiltrating and navigating the system. Future directions for social justice and advocacy in counselling psychology are discussed in relation to systemic change.